Investigation on difference in auto-toxicity among tobacco cultivars - XU Lu-lu; PAN Wen-jie; ZHANG Guo-ping (浙江大学学报. 农业与生命科学版)
The differences among eight tobacco culitvars or lines (Nicotiana tabacum) in auto-toxicity of root exudates were investigated using bioassay. Root exudates of the eight tobacco cultivars or lines were collected and used to determine the effects of them on seed germination and seedling growth. The results showed that for most cultivars, fresh and dry mass, leaf and root length were increased at low concentration of exudate and reduced at high concentration of one. A cultivar, Qianxi 1 showed the greatest inhibition for all growth parameters above. While the breeding line, No.1 was quite particular in its response to root exudate, in that all growth parameters showed increase, even under the highest concentration of root exudate. Germination rate of the new lines No. 7, No. 1 and cultivars Yunyan 85 and Chunlei 3 were promoted, while that of other cultivars was inhibited by root exudates. It may be concluded that that the auto-toxicity differs among tobacco genotypes, suggesting that it is possible in breeding program to develop the cultivars with less allelopathy.